Preparation method of high-temperature wear-resistant corrosion-resistant anti-coking high-entropy boron nitride ceramic material

By adopting the preparation method of high-entropy boron nitride ceramic materials, combined with high-entropy metal alloys, graphene and metal organic frame materials, the problem of insufficient durability of existing high-temperature ceramic materials has been solved, and the high-temperature stability, corrosion resistance and coking resistance have been significantly improved.

CN119913389APending Publication Date: 2025-05-02雷品越
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510101669.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Existing high-temperature ceramic materials lack durability in extremely high temperature, wear, corrosion and coking environments, making it difficult to work stably for a long time in complex industrial environments.

Method used

Using the preparation method of high-entropy boron nitride ceramic materials, the preparation method is prepared by mixing boron nitride powder with high-entropy metal alloy precursor, adding graphene, boride, silicate ceramics and transition metal compounds, as well as metal organic frame materials as self-healing components, and preparing through co-precipitation method, nitriding treatment, thermal isostatic sintering and plasma-enhanced chemical vapor deposition technology.

Benefits of technology

It significantly improves the high temperature stability, corrosion resistance and coking resistance of the material, enhances the self-healing ability of the material and the surface corrosion resistance, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913389A_ABST
    Figure CN119913389A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high-temperature materials, and discloses a preparation method of a high-temperature wear-resistant corrosion-resistant anti-coking high-entropy boron nitride ceramic material. The preparation method comprises the following steps: S1, mixing boron nitride powder with a high-entropy metal alloy precursor; s2, adding graphene into the mixture to serve as a two-dimensional material, wherein the weight ratio of the graphene to the two-dimensional material is 5-10%; s3, boride, silicate ceramic and a transition metal compound are added into the mixture, and the weight ratio is 5-15%; and S4, adding a self-repairing component, wherein the self-repairing component accounts for 5-10% of the weight of the metal organic framework material. By adopting the technical scheme of compounding the high-entropy alloy and the boron nitride, the effect of improving the high-temperature stability and the corrosion resistance of the material is achieved. Compared with the scheme that a single metal alloy is adopted in the prior art, through the synergistic effect of the multi-element alloy, the problems that the alloy is prone to phase separation and poor in corrosion resistance at the high temperature are solved, and the application performance of the material in the extreme environment is remarkably enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-temperature materials, and in particular to a preparation method of a high-temperature anti-wear, anti-corrosion and anti-coking high-entropy boron nitride ceramic material. Background Art

[0002] In the current high-temperature material technology, wear-resistant, corrosion-resistant and coking-resistant ceramic materials are widely used in industrial fields under high temperature and harsh environments, especially in high-temperature environments such as metallurgy and petrochemicals, where materials face challenges such as high-temperature corrosion, wear and coking. In order to improve the long-term stability and service life of materials, researchers have been working hard to improve the performance of ceramic materials, especially in terms of thermal stability, mechanical properties, corrosion resistance and self-healing ability.

[0003] Traditional ceramic materials, such as boron nitride ceramics, show excellent heat resistance and oxidation resistance under high temperature conditions, but they are brittle and easily cracked and damaged by thermal stress and external forces at high temperatures. In addition, the performance of boron nitride ceramics in high-temperature corrosive environments, especially in the presence of corrosive gases such as sulfur and chlorine, still faces great challenges, and it is difficult to achieve long-term stable operation.

[0004] Most high-temperature ceramics in the prior art are designed with a single metal alloy. Although these materials can provide certain strength and corrosion resistance, due to the small number of alloy elements, it is difficult to fully optimize the high-temperature performance of the material, especially in terms of thermal stability and anti-coking at high temperatures. When facing a complex environment, a single metal alloy often has difficulty in achieving an ideal balance of performance, resulting in poor overall stability of the material.

[0005] The prior art introduces two-dimensional materials such as graphene to enhance the thermal conductivity and crack resistance of materials, but the incremental use of graphene is limited and its excellent thermal conductivity and mechanical properties cannot be fully utilized. In addition, the prior art still has problems in controlling the dispersion uniformity and compatibility of graphene, and has not completely solved the problem that ceramic materials are prone to cracking at high temperatures.

[0006] Nitrides and metal ceramics are resistant to high temperatures and oxidation to a certain extent, but their corrosion resistance is still significantly limited in high-temperature environments containing corrosive gases such as sulfur and chlorine. Traditional anti-corrosion technology is difficult to provide comprehensive protection for ceramic materials, especially in complex industrial environments, where materials often exhibit high corrosion rates in a short period of time. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention provides a method for preparing a high-temperature, wear-resistant, corrosion-resistant and coking-resistant high-entropy boron nitride ceramic material, which solves the problem of insufficient durability of existing high-temperature ceramic materials in extremely high temperature, wear, corrosion and coking environments.

[0008] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing a high-temperature anti-wear, anti-corrosion and anti-coking high-entropy boron nitride ceramic material, comprising the following steps;

[0009] S1, mixing boron nitride powder with a high entropy metal alloy precursor;

[0010] S2, adding graphene as a two-dimensional material to the mixture, with a weight percentage of 5-10%;

[0011] S3, adding boride, silicate ceramic and transition metal compound to the above mixture, accounting for 5-15% by weight;

[0012] S4, adding a self-repairing component, wherein the self-repairing component is a metal organic framework material accounting for 5 to 10% by weight;

[0013] S5, preparing a precursor by a co-precipitation method using the mixture to obtain a high entropy nitride precursor;

[0014] S6, performing nitridation treatment on the precursor to obtain a high entropy boron nitride ceramic composite material;

[0015] S7, using hot isostatic pressing technology to perform sintering to obtain a high-temperature anti-wear, anti-corrosion, and anti-coking high-entropy boron nitride ceramic material;

[0016] S8. Perform surface modification on the sintered material to form a protective layer with self-repairing function.

[0017] Preferably, the high entropy metal alloy in step S1 comprises the following components by weight: 5-8% titanium, 2-4% aluminum, 3-5% chromium, 2-3% vanadium, 2-4% zirconium, 2-3% niobium, 2-3% hafnium, 3-5% molybdenum, and 2-3% tungsten.

[0018] Preferably, in the co-precipitation method in step S5, the pH value of the solution is in the range of 4 to 7, and the precipitation temperature of the precursor is in the range of 50 to 80°C.

[0019] Preferably, the precursor drying temperature in the coprecipitation method is in the range of 100 to 150° C., and the drying time is 6 to 12 hours.

[0020] Preferably, the atmosphere for the nitridation treatment in step S6 is an ammonia atmosphere, the temperature is 1000-1500° C., and the nitridation time is 2-6 hours.

[0021] Preferably, the temperature of the nitriding treatment is 1200-1400° C., and the nitriding time is 3-5 hours.

[0022] Preferably, the sintering temperature range of the hot isostatic pressing technology in step S7 is 1600-1800° C., the sintering pressure is 30-150 MPa, the sintering time is 1-4 hours, and the sintering atmosphere is argon or nitrogen protective atmosphere.

[0023] Preferably, the surface modification step in step S8 is performed by a plasma enhanced chemical vapor deposition method, the deposition atmosphere is a mixed gas of argon and nitrogen, the deposition temperature ranges from 400 to 600° C., and the deposition time is 2 to 6 hours.

[0024] Preferably, the specific steps in step S8 include:

[0025] S8.1, pretreating the sintered high entropy boron nitride ceramic composite material to remove surface contaminants;

[0026] S8.2. Use plasma enhanced chemical vapor deposition technology to deposit metal organic framework materials or self-healing polymers in a high temperature atmosphere to form a uniform surface protective layer;

[0027] S8.3. Control the thickness of the surface layer to ensure good bonding strength and corrosion resistance. The thickness of the surface repair layer ranges from 2μm to 10μm.

[0028] Preferably, the self-healing component in step S8 is a metal organic framework material, and the types of metal organic framework materials include but are not limited to copper-based, zinc-based or aluminum-based materials.

[0029] The invention provides a method for preparing a high-temperature wear-resistant, corrosion-resistant and coking-resistant high-entropy boron nitride ceramic material.

[0030] It has the following beneficial effects:

[0031] 1. The present invention achieves the effect of improving the high temperature stability and corrosion resistance of the material by adopting the technical solution of high entropy alloy and boron nitride composite. Compared with the solution of using a single metal alloy in the prior art, the present invention solves the problem of easy phase separation and poor corrosion resistance of the alloy at high temperature through the synergistic effect of multi-element alloy, and significantly enhances the application performance of the material in extreme environments.

[0032] 2. The present invention achieves the effect of improving thermal conductivity and crack resistance and enhancing material toughness by introducing graphene as a two-dimensional material to enhance the structure of ceramic composite materials. Compared with the conventional materials in the prior art that lack thermal management capabilities, the use of graphene significantly reduces the accumulation of thermal stress, effectively prevents the brittle cracking of materials under high temperature conditions, and improves the stability of the overall structure.

[0033] 3. The present invention uses metal organic framework materials as self-repairing components to achieve the self-repairing ability of materials under high temperature conditions. Compared with the ceramic materials in the prior art that cannot self-repair, the present invention solves the problem of reduced durability of traditional materials due to microcrack expansion through the self-repairing effect of MOFs, allowing the material to maintain its functionality for a long time in a high temperature environment.

[0034] 4. The present invention improves the density and surface corrosion resistance of ceramic composite materials by adopting hot isostatic pressing sintering and plasma enhanced chemical vapor deposition technology. Compared with the materials of conventional sintering technology in the prior art, the present invention reduces the pores in the material through hot isostatic pressing technology, improves the density after sintering, and the surface modification provides an additional protective layer, which significantly enhances the anti-coking and corrosion resistance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a flow chart of the preparation method of the present invention. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Please refer to the attached Figure 1 The embodiment of the present invention provides a method for preparing a high-temperature wear-resistant, corrosion-resistant and coking-resistant high-entropy boron nitride ceramic material, comprising the following steps:

[0038] S1, mixing boron nitride powder with a high entropy metal alloy precursor;

[0039] S2, adding graphene as a two-dimensional material to the mixture, with a weight percentage of 5-10%;

[0040] S3, adding boride, silicate ceramic and transition metal compound to the above mixture, accounting for 5-15% by weight;

[0041] S4, adding a self-repairing component, wherein the self-repairing component is a metal organic framework material accounting for 5 to 10% by weight;

[0042] S5, preparing a precursor by a co-precipitation method using the mixture to obtain a high entropy nitride precursor;

[0043] S6, performing nitridation treatment on the precursor to obtain a high entropy boron nitride ceramic composite material;

[0044] S7, using hot isostatic pressing technology to perform sintering to obtain a high-temperature anti-wear, anti-corrosion, and anti-coking high-entropy boron nitride ceramic material;

[0045] S8. Perform surface modification on the sintered material to form a protective layer with self-repairing function.

[0046] Example 1

[0047] step;

[0048] Precursor preparation;

[0049] Boron nitride powder (40%) was mixed evenly with high entropy metal alloy precursors (titanium 5%, aluminum 3%, chromium 4%, vanadium 2%, zirconium 3%, niobium 2%, hafnium 2%, molybdenum 4%, tungsten 3%). A ball mill was used for mixing to ensure that the metal elements and the boron nitride powder were evenly distributed.

[0050] Adding graphene;

[0051] Graphene (6%) was added to the mixture and dispersed using an ultrasonic disperser to ensure that the graphene was evenly distributed.

[0052] adding borides and transition metal compounds;

[0053] 10% of boride and 4% of transition metal compound were added. Further mixing was performed using a grinder.

[0054] The addition of self-healing ingredients;

[0055] 8% of metal organic framework materials (MOFs) are added to the above mixture, mainly aluminum-based MOFs, to ensure that they can form a self-healing layer in subsequent processes.

[0056] The precursor was prepared by coprecipitation method;

[0057] The mixture is reacted with ammonia water and treated by co-precipitation method. The pH value is controlled at about 5, the precipitation temperature is maintained at 60° C., and the reaction is carried out for 6 hours to obtain a high entropy nitride precursor.

[0058] Nitriding treatment;

[0059] The obtained precursor was placed in an ammonia atmosphere for nitridation, the temperature was set to 1300° C., and the nitridation time was 4 h.

[0060] Hot isostatic pressing sintering;

[0061] Hot isostatic pressing technology was used for sintering, the sintering temperature was set to 1700°C, the pressure was 100 MPa, the sintering time was maintained at 3 h, and the atmosphere was argon.

[0062] Surface modification;

[0063] The surface modification was carried out by plasma enhanced chemical vapor deposition method. The deposition temperature was 500°C, the deposition time was 4h, and the atmosphere was a mixture of argon and nitrogen.

[0064] Example 2

[0065] step;

[0066] Precursor preparation;

[0067] Boron nitride powder (50%) was mixed with a high entropy metal alloy precursor (6% titanium, 3% aluminum, 4% chromium, 5% molybdenum, 2% tungsten, and 2% zirconium) and uniformly ball-milled for 30 minutes.

[0068] Adding graphene;

[0069] Graphene (5%) was added and sonicated for 5 minutes to ensure that it was evenly dispersed in the mixture.

[0070] adding borides and transition metal compounds;

[0071] 10% of a boride (such as boron chloride) and 6% of a transition metal compound (such as sodium molybdate) are added and secondary grinding is performed.

[0072] Add self-repairing ingredients;

[0073] Add 7% metal organic framework material, preferably copper-based MOFs, and stir at high speed to ensure that the MOFs are evenly distributed.

[0074] The precursor was prepared by coprecipitation method;

[0075] After the above mixture was dissolved, the precursor was prepared by co-precipitation method, the pH value was controlled at 6-7, the temperature was controlled at 70°C, and the precipitation time was 4h.

[0076] Nitriding treatment;

[0077] The atmosphere was ammonia, the temperature was set to 1200 °C, and the nitriding time was 3 h.

[0078] Hot isostatic pressing (HIP) sintering;

[0079] Hot isostatic pressing was used for sintering, with the temperature set at 1800°C, the pressure at 120 MPa, the sintering time at 2 h, and the sintering atmosphere at nitrogen.

[0080] Surface modification;

[0081] The surface modification was carried out by PECVD method, the deposition temperature was 450°C, the deposition atmosphere was a mixture of argon and nitrogen, and the deposition time was 3 h.

[0082] Example 3

[0083] step;

[0084] Precursor preparation;

[0085] Boron nitride powder (45%) was mixed with a high entropy metal alloy precursor (7% titanium, 3% aluminum, 4% chromium, 3% tungsten, and 3% vanadium), and the mixture was thoroughly mixed for 30 minutes using a stirrer.

[0086] Adding graphene;

[0087] Graphene (8%) was added and high shear dispersion technology was used to ensure that the graphene was evenly dispersed.

[0088] Addition of borides and transition metal compounds;

[0089] Add 9% boride (such as boron chloride) and 4% sodium molybdate, and continue grinding to ensure that the additives are fully mixed.

[0090] The addition of self-healing ingredients;

[0091] 10% of metal organic framework materials (MOFs) are added, and aluminum-based MOFs are selected to ensure good self-healing properties.

[0092] The precursor was prepared by coprecipitation method;

[0093] The co-precipitation was carried out in ammonia water, the pH value was set to 5, the precipitation temperature was maintained at 75°C, and the reaction was carried out for 5 hours to obtain a precursor.

[0094] Nitriding treatment;

[0095] The precursor was placed in an ammonia atmosphere for nitridation, the temperature was set to 1400°C, and the nitridation time was 4 hours.

[0096] Hot isostatic pressing (HIP) sintering;

[0097] Hot isostatic pressing technology was used for sintering, with a sintering temperature of 1700°C, a pressure of 100 MPa, a sintering time of 3 h, and an argon protective atmosphere.

[0098] Surface modification;

[0099] The PECVD method was used for surface modification, the deposition temperature was 500°C, the deposition atmosphere was a mixture of argon and nitrogen, and the deposition time was 4 h.

[0100] Example 4

[0101] step;

[0102] Precursor preparation;

[0103] Boron nitride powder (50%) was mixed with a high entropy metal alloy precursor (titanium 5%, aluminum 4%, chromium 3%, molybdenum 5%, tungsten 3%) and stirred evenly for 30 minutes.

[0104] Adding graphene;

[0105] Graphene (7%) was added and evenly dispersed using ultrasonic treatment technology.

[0106] adding borides and transition metal compounds;

[0107] 12% of a boride (such as boron chloride) and 5% of a transition metal compound (such as sodium molybdate) are added and mixed again using a grinder.

[0108] Add self-repairing ingredients;

[0109] Metal organic framework materials (MOFs) are added, with zinc-based MOFs being selected at a ratio of 6% to enhance the self-healing ability.

[0110] The precursor was prepared by coprecipitation method;

[0111] The precursor was synthesized by co-precipitation method, the solution pH was maintained at 6, the temperature was set at 60 °C, and the reaction time was 5 h.

[0112] Nitriding treatment;

[0113] The nitridation was carried out in an ammonia atmosphere, the temperature was set to 1300°C, and the nitridation time was 3 h.

[0114] Hot isostatic pressing (HIP) sintering;

[0115] Hot isostatic pressing was used for sintering, with the temperature set at 1750°C, the pressure at 120 MPa, the sintering time at 2 h, and the argon protective atmosphere.

[0116] Surface modification;

[0117] The PECVD method was used for surface modification, the deposition temperature was 470°C, the deposition atmosphere was a mixture of argon and nitrogen, and the deposition time was 3 h.

[0118] Comparative Example 1

[0119] Example 1: In Example 1, we used high entropy metal alloys (a combination of elements such as titanium, aluminum, chromium, vanadium, zirconium, niobium, hafnium, molybdenum and tungsten) and self-healing components such as graphene (6%) and metal organic framework materials. The main processes include co-precipitation, nitridation, hot isostatic pressing and plasma enhanced chemical vapor deposition (PECVD) surface modification technology. Through these steps, a composite ceramic material with self-healing function and excellent high temperature performance was successfully prepared.

[0120] Comparative Example 1;

[0121] In comparative example 1, all process steps remain the same, but the proportion of graphene is only 2%, and the metal organic framework material is not used. The remaining components and process conditions are not changed, and the high entropy metal alloy is still used and the same nitridation treatment and hot isostatic pressing sintering technology are adopted.

[0122] Description of the difference;

[0123] The proportion of graphene decreases; the reduction in the proportion of graphene will lead to lower thermal conductivity and crack resistance of the material, especially in high temperature environments, the crack resistance of the material will be greatly reduced.

[0124] Lack of metal-organic framework materials; The omission of the use of metal-organic framework materials results in the lack of self-healing function of the materials, and they cannot be effectively repaired when microcracks appear, thereby reducing the service life and reliability of the materials.

[0125] Comparative Example 2

[0126] Example 2: In Example 2, we used boron nitride powder (50%) and high entropy metal alloys (titanium, aluminum, chromium, molybdenum, tungsten, etc.), as well as graphene (5%) and metal organic framework materials as self-healing components (8%). The precursor was prepared by coprecipitation and nitrided in an ammonia atmosphere. Finally, hot isostatic pressing technology was used for sintering and PECVD method was used for surface modification.

[0127] Comparative Example 2;

[0128] Comparative Example 2 maintained the same high entropy metal alloy and boron nitride powder ratio, but changed the graphene ratio to 10%, and did not use metal organic framework materials. During the coprecipitation and nitridation process, the temperature, time, and atmosphere conditions were completely consistent.

[0129] Description of the difference;

[0130] The proportion of graphene increases; increasing the proportion of graphene may improve the thermal conductivity of the material, but due to the lack of self-repairing metal organic framework materials, the durability and crack resistance of the material are relatively poor, and it is easy to crack during high-temperature use.

[0131] Lack of metal-organic framework materials; without metal-organic framework materials, surface and internal cracks cannot self-repair, which increases the risk of material breakage and cannot solve the life problem of materials under long-term high-temperature use in existing technologies.

[0132] Comparative Example 3

[0133] Example 3: In Example 3, boron nitride powder (45%) is mixed with a high entropy metal alloy (titanium, aluminum, chromium, molybdenum, tungsten in equal proportions) and graphene (8%), a metal organic framework material (6%) is added as a self-healing component, and the precursor is prepared by a co-precipitation method. The nitridation treatment temperature is 1400°C, and hot isostatic pressing (1700°C) and PECVD surface modification technology (500°C) are subsequently carried out.

[0134] Comparative Example 3;

[0135] In Comparative Example 3, the ratio of boron nitride powder to high entropy metal alloy remains unchanged, but graphene is reduced to 4%, and a lower ratio of metal organic framework material (3%) is used, and the process steps, nitridation temperature and sintering parameters remain consistent.

[0136] Description of the difference;

[0137] The proportion of graphene is reduced; reducing the proportion of graphene will reduce the thermal conductivity and crack resistance of the composite material, especially in high temperature environment, the material's crack resistance is poor, and it is easy to crack or be damaged.

[0138] The proportion of metal-organic framework materials decreases; the self-healing ability decreases, and the life of the material will be limited under high temperature or long-term use, especially when microcracks occur and cannot be repaired.

[0139] Comparative Example 4

[0140] Example 4: In Example 4, boron nitride powder (50%) was mixed with a high entropy metal alloy (titanium, aluminum, chromium, molybdenum, tungsten, etc.), and graphene (7%) and metal organic framework materials (MOFs, 8%) were added to enhance the self-healing ability of the material. This step was followed by coprecipitation, nitridation (1400°C, 3h) and hot isostatic pressing (1750°C, 120MPa), and finally PECVD surface modification.

[0141] Comparative Example 4;

[0142] The change of Comparative Example 4 is that the proportion of graphene is increased to 10%, and no metal organic framework material is used. The remaining components and process parameters are the same as those of Example 4.

[0143] Description of the difference;

[0144] The proportion of graphene increases; the increase of graphene may bring about a certain improvement in thermal conductivity, but the lack of self-healing function caused by the lack of metal-organic framework materials greatly affects the long-term stability of the material.

[0145] Lack of metal organic framework materials; without the self-repairing layer of the metal organic framework material, the material cannot repair micro cracks during high temperature use, reducing its service life and fatigue resistance. The lack of this function makes the high temperature performance of the material more fragile than the embodiment.

[0146] Experiment 1: High temperature anti-coking test

[0147] Experimental procedures;

[0148] Sample preparation;

[0149] Example 1: Boron nitride powder (40%) was mixed with a high entropy metal alloy precursor (a synthetic ratio of elements such as titanium, aluminum, chromium, vanadium, zirconium, niobium, hafnium, molybdenum and tungsten) and uniformly mixed using a ball mill for 30 minutes.

[0150] Comparative Example 1: Same as Example 1, the metal alloy ratio is consistent, but the graphene ratio is reduced to 2%, and no metal organic framework material is added.

[0151] Sample preparation process;

[0152] Graphene (6%) and metal organic framework materials (MOFs, 8%) were added to the above mixture, and ultrasonic treatment technology was used to ensure that the graphene was evenly dispersed and the activity of the MOFs was maintained.

[0153] Atmosphere simulation;

[0154] Set up a simulated high temperature environment in an electric furnace. Place the prepared sample in the furnace, set the temperature to 850°C, and use a coal gas environment (sulfur-containing gas). Set the heating time to 30 hours to simulate a high temperature corrosion environment.

[0155] test;

[0156] The surface of the samples was observed using a scanning electron microscope (SEM) to record the formation of the coking layer.

[0157] The mass loss of the sample is measured by mass analysis test.

[0158] Use mechanical testing to measure the adhesion between the coking layer and the base material and observe whether there is any shedding phenomenon.

[0159] Data collection;

[0160] Quantitatively analyze the effect of coking on the sample surface and evaluate the degree of coking formation and its adhesion to the substrate material;

[0161] Experimental data;

[0162] Table name: High temperature anti-coking test results

[0163] Sample No. Coking layer thickness (μm) Mass loss (g) Adhesion(N) Example 1 120 0.25 10.5 Comparative Example 1 350 0.35 4.8 Example 1 100 0.20 11.2 Comparative Example 1 400 0.40 5.2 Example 1 115 0.28 9.7 Comparative Example 1 375 0.38 5.0

[0164] Summarize;

[0165] The experimental results show that the thickness and mass loss of the coking layer of Example 1 under high temperature conditions are significantly lower than those of Comparative Example 1. The introduction of graphene and metal organic framework materials (MOFs) significantly improves the anti-coking performance. The high thermal conductivity of graphene enables heat to be evenly distributed in the ceramic matrix, reducing local overheating, thereby effectively slowing down the formation of coking.

[0166] The addition of graphene enhances the thermal conductivity of the material and reduces the accumulation of thermal stress at high temperatures, which helps maintain the integrity of the material and reduce the occurrence of coking. The self-healing ability of MOFs forms a stable protective layer, so that surface microcracks can be repaired even at high temperatures, thereby preventing further expansion of the coking layer. The coking layer of the material in Example 1 has strong adhesion at high temperatures and can effectively resist the accumulation of coking materials at high temperatures.

[0167] Experiment 2: High temperature corrosion resistance test

[0168] Experimental procedures;

[0169] Sample preparation;

[0170] Example 2: Prepare boron nitride powder (50%) and high entropy metal alloy (titanium, aluminum, chromium, molybdenum, tungsten, etc.), graphene (5%), and metal organic framework material (MOFs, 8%). Mix the boron nitride and metal alloy powders, ensure uniformity, add graphene and disperse by ultrasonic, and finally add MOFs and stir evenly.

[0171] Comparative Example 2: The same ratio of high entropy metal alloy to boron nitride powder was used, but the ratio of graphene was increased to 10%, and the addition of MOFs was omitted.

[0172] Atmosphere simulation and high temperature oxidation;

[0173] The prepared samples were placed in a high-temperature furnace, an oxidizing atmosphere (a mixture of 5% oxygen and nitrogen) was set, the temperature was set to 1000°C, and the samples were continuously exposed for 48 hours to simulate a high-temperature corrosion environment.

[0174] The oxygen content is controlled at 5% to ensure that the material is subjected to true oxidation conditions at high temperatures.

[0175] Testing methods;

[0176] Corrosion rate: Use an electrochemical workstation to test corrosion potential and corrosion current density to quantify the corrosion resistance of the material.

[0177] Mass loss: Measure the mass change of the sample by weighing and evaluate the loss of the material in a corrosive environment.

[0178] Surface observation: Use a scanning electron microscope (SEM) to observe the surface corrosion of the sample and analyze the corrosion mechanism of the material and the surface morphology after corrosion.

[0179] Data recording and processing;

[0180] After the test, the corrosion resistance of the two groups of samples was analyzed by SEM images, mass loss and electrochemical parameters to further verify the contribution of graphene and MOFs to the corrosion resistance of the materials;

[0181] Experimental data;

[0182] Table name: High temperature corrosion resistance test results

[0183]

[0184] Summarize;

[0185] Example 2 significantly improves the corrosion resistance of the material by using a combination of graphene and metal organic framework materials (MOFs). The corrosion current density of Example 2 is significantly lower than that of Comparative Example 2, indicating that its corrosion rate is slower and the surface corrosion phenomenon is lighter. Through SEM observation, the surface corrosion layer of Example 2 is thinner and no large area of ​​corrosion pits appear, while the surface corrosion layer of Comparative Example 2 is thicker and the corrosion depth is greater.

[0186] The introduction of graphene improves the thermal conductivity and mechanical strength of the material, slows down the accumulation of corrosive substances on the surface of the material, which enables the material to maintain good corrosion resistance in a high temperature environment. The use of MOFs enhances the surface protection ability of the material. Its high surface area and chemical activity enable it to play a self-repairing function during the corrosion process, further reducing the formation of the corrosion layer. Therefore, Example 2 shows better corrosion resistance than Comparative Example 2, reducing the corrosion loss of traditional materials under harsh high temperature conditions.

[0187] Experiment 3: Wear resistance and hardness test

[0188] Experimental procedures;

[0189] Sample preparation;

[0190] Example 3: Boron nitride powder (45%) and high entropy metal alloy (titanium, aluminum, chromium, molybdenum, tungsten, etc. are mixed in proportion), and graphene (8%) and metal organic framework material (MOFs, 6%) are added. After the mixture is uniform, the graphene is dispersed by ultrasonic treatment technology to ensure its uniform distribution. The final mixture is subjected to coprecipitation to prepare a precursor.

[0191] Comparative Example 3: The same ratio of high entropy metal alloy and boron nitride powder as in Example 3 was used, but the graphene ratio was changed to 4%, and MOFs was not used as a self-healing component.

[0192] Atmosphere simulation and high temperature wear test;

[0193] In the high temperature friction and wear tester, the sample is placed on the friction disc, the load is set to 20N, the sliding speed is set to 0.3m / s, and the temperature is 600°C. This test condition simulates the friction and wear conditions in a high temperature environment.

[0194] Testing methods;

[0195] Friction coefficient: The friction coefficient was recorded in real time using a friction and wear testing machine, with data recorded every 5 minutes during the test.

[0196] Hardness: Use Vickers hardness tester to carry out hardness test and record the hardness change of sample in high temperature wear environment.

[0197] Wear volume: The mass loss of the sample is measured by a precision balance to evaluate the wear rate of the material at high temperature.

[0198] Data recording and analysis;

[0199] The test data will be used to compare the friction coefficient, hardness and wear amount of Example 3 and Comparative Example 3 under high temperature conditions, and to analyze the contribution of graphene and MOFs in improving hardness and wear resistance.

[0200] Experimental data;

[0201] Table name: High temperature wear resistance and hardness test results

[0202]

[0203]

[0204] Summarize;

[0205] Example 3 exhibits a lower friction coefficient and higher hardness under high temperature conditions, indicating that it has significant advantages in wear resistance and abrasion resistance. Compared with Comparative Example 3, Example 3 has lower mass loss and significantly higher hardness, indicating that the wear resistance of the composite material is improved by the combined action of graphene and metal organic framework materials (MOFs).

[0206] The introduction of graphene significantly improves the thermal conductivity and mechanical strength of the material, and reduces wear in high-temperature environments. MOFs, as a self-healing component, can form a protective film on the surface of the material during the wear process, reduce the expansion of cracks, and further improve the service life of the material. The self-healing effect of MOFs enables the material to repair microcracks during the wear process, avoid crack expansion, and extend the wear resistance and hardness of the material.

[0207] Experiment 4: Self-repair capability test

[0208] Experimental procedures;

[0209] Sample preparation;

[0210] Example 4: Prepare boron nitride powder (50%) and high entropy metal alloy (titanium, aluminum, chromium, molybdenum, tungsten, etc.), add graphene (7%) and metal organic framework material (MOFs, 8%). After mixing these ingredients, ultrasonic treatment is used to ensure that graphene is completely dispersed and MOFs are evenly distributed.

[0211] Comparative Example 4: Using the same ratio of high entropy metal alloy and boron nitride powder, the graphene ratio was increased to 10%, but MOFs were not used.

[0212] Damage simulation;

[0213] Artificial microcracks are applied to the sample surface, using a fine scraper or laser etching technology to create microcracks with a depth of 0.1 mm to simulate the damage to the material surface under high temperature environment.

[0214] High temperature repair environment;

[0215] The damaged samples were placed in an environment of 1000°C to simulate the self-repair process of surface cracks in materials under high temperature conditions. The samples were exposed to the atmosphere for 1 hour and the repair conditions were observed.

[0216] Fix test;

[0217] Crack recovery degree: The crack recovery was observed using a scanning electron microscope (SEM). The samples were taken out every 10 minutes and the crack recovery at different time points was photographed.

[0218] Repair efficiency: By measuring the change in crack width, the repair efficiency is calculated and the gradual filling of cracks during the repair process is recorded.

[0219] Data recording;

[0220] The time, degree and efficiency of crack recovery were recorded to ensure that the changes in the self-healing process were fully captured. The self-healing ability of the sample was quantitatively analyzed based on the recovery observed in each experiment.

[0221] Experimental data;

[0222] Table name: Self-repair capability test results

[0223]

[0224] Summarize;

[0225] The self-repairing ability of Example 4 is significantly better than that of Comparative Example 4, especially in terms of efficiency and speed of crack recovery. The MOFs materials in Example 4 provide a key self-repairing effect, as they can react with external gases in a high temperature environment to form new substances, thereby filling cracks and repairing surface damage.

[0226] The self-healing function absorbs external gases through its highly open structure and reacts at the cracks to form new substances, which fill the cracks and repair the surface. Graphene slows down the accumulation of thermal stress by enhancing the thermal conductivity and mechanical strength of the material, avoiding the rapid expansion of cracks and further damage.

[0227] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-temperature anti-wear, anti-corrosion and anti-coking high-entropy boron nitride ceramic material, characterized in that: The steps include: S1, mixing boron nitride powder with a high entropy metal alloy precursor; S2, adding graphene as a two-dimensional material to the mixture, with a weight percentage of 5-10%; S3, adding boride, silicate ceramic and transition metal compound to the above mixture, accounting for 5-15% by weight; S4, adding a self-repairing component, wherein the self-repairing component is a metal organic framework material accounting for 5 to 10% by weight; S5, preparing a precursor by a co-precipitation method using the mixture to obtain a high entropy nitride precursor; S6, performing nitriding treatment on the precursor to obtain a high entropy boron nitride ceramic composite material; S7, using hot isostatic pressing technology to perform sintering to obtain a high-temperature wear-resistant, corrosion-resistant, and coking-resistant high-entropy boron nitride ceramic material; S8. Perform surface modification on the sintered material to form a protective layer with self-repairing function.

2. The method for preparing a high-temperature anti-wear, anti-corrosion and anti-coking high-entropy boron nitride ceramic material according to claim 1, characterized in that: The high entropy metal alloy in step S1 comprises the following components by weight: 5-8% titanium, 2-4% aluminum, 3-5% chromium, 2-3% vanadium, 2-4% zirconium, 2-3% niobium, 2-3% hafnium, 3-5% molybdenum, and 2-3% tungsten.

3. The method for preparing a high-temperature anti-wear, anti-corrosion and anti-coking high-entropy boron nitride ceramic material according to claim 1, characterized in that: In the co-precipitation method in step S5, the pH value of the solution is in the range of 4 to 7, and the precipitation temperature of the precursor is in the range of 50 to 80°C.

4. The method for preparing a high-temperature anti-wear, anti-corrosion and anti-coking high-entropy boron nitride ceramic material according to claim 1, characterized in that: The precursor drying temperature in the coprecipitation method ranges from 100 to 150° C., and the drying time ranges from 6 to 12 hours.

5. The method for preparing a high-temperature anti-wear, anti-corrosion and anti-coking high-entropy boron nitride ceramic material according to claim 1, characterized in that: The atmosphere of the nitridation treatment in step S6 is an ammonia atmosphere, the temperature is 1000-1500° C., and the nitridation time is 2-6 hours.

6. The method for preparing a high-temperature anti-wear, anti-corrosion and anti-coking high-entropy boron nitride ceramic material according to claim 1, characterized in that: The temperature of the nitriding treatment is 1200-1400° C., and the nitriding time is 3-5 hours.

7. The method for preparing a high-temperature anti-wear, anti-corrosion and anti-coking high-entropy boron nitride ceramic material according to claim 1, characterized in that: The sintering temperature range of the hot isostatic pressing technology in step S7 is 1600-1800° C., the sintering pressure is 30-150 MPa, the sintering time is 1-4 hours, and the sintering atmosphere is argon or nitrogen protective atmosphere.

8. The method for preparing a high-temperature anti-wear, anti-corrosion and anti-coking high-entropy boron nitride ceramic material according to claim 1, characterized in that: The surface modification step in step S8 is performed by a plasma enhanced chemical vapor deposition method, the deposition atmosphere is a mixed gas of argon and nitrogen, the deposition temperature ranges from 400 to 600° C., and the deposition time is 2 to 6 hours.

9. The method for preparing a high-temperature anti-wear, anti-corrosion and anti-coking high-entropy boron nitride ceramic material according to claim 1, characterized in that: The specific steps in step S8 include: S8.1, pretreating the sintered high entropy boron nitride ceramic composite material to remove surface contaminants; S8.

2. Use plasma enhanced chemical vapor deposition technology to deposit metal organic framework materials or self-healing polymers in a high temperature atmosphere to form a uniform surface protective layer; S8.

3. Control the thickness of the surface layer to ensure good bonding strength and corrosion resistance. The thickness of the surface repair layer ranges from 2μm to 10μm.

10. The method for preparing a high-temperature anti-wear, anti-corrosion and anti-coking high-entropy boron nitride ceramic material according to claim 1, characterized in that: The self-repairing component in step S8 is a metal organic framework material, and the types of metal organic framework materials include but are not limited to copper-based, zinc-based or aluminum-based materials.